Progress in Perovskite Solar Cells towards Commercialization—A Review - Hongqiao Wang (MDPI AG, 2021)
In recent years, perovskite solar cells (PSCs) have experienced rapid development and have presented an excellent commercial prospect as the PSCs are made from raw materials that are readily and cheaply available depending on simple manufacturing techniques. However, the commercial production and utilization of PSCs remain immature, leading to substantial efforts needed to boost the development of scalable fabrication of PSCs, pilot scale tests, and the establishment of industrial production lines. In this way, the PSCs are expected to be successfully popularized from the laboratory to the photovoltaic market. In this review, the history of power conversion efficiency (PCE) for laboratory-scale PSCs is firstly introduced, and then some methods for maintaining high PCE in the upscaling process is displayed. The achievements in the stability and environmental friendliness of PSCs are also summarized because they are also of significance for commercialization. Finally, this review evaluates the commercialization prospects of PSCs from the economic view and provides a short outlook.